Pola Pertumbuhan Gastropoda Monetaria annulus di Teluk Doreri - Yuventus Wale Wake; Roni Bawole; Emmanuel Manangkalangi; Luky Sembel; Ridwan Sala (Jurnal Kelautan Tropis, 2022)
Manokwari coastal waters are one of the coastal areas that experience very rapid development of development activities from year to year. This condition can disrupt the ecosystem and can also interfere with the growth of gastropods, especially Monetaria annulus. This research was conducted in three locations (Yenkarwar Beach, Nusmapi Island, and Tanjung Manggewa) for two months (October and November 2020). The purpose of this study was to describe the relationship between length and weight, as well as the growth pattern of the gastropod M. annulus in Doreri Bay. Data was collected using a square with a length of 100 m with a width adjusted to the width of the seagrass bed towards the sea. Especially for the location of the waters of Yenkarwar Beach, no individual M. annulus was found during the sampling. The results showed a relationship between length and weight at the locations of Nusmapi I. and Tanjung Manggewa, respectively, namely BT = 0.0017PC2.3883 and BT = 0.0005PC2.8188. The growth pattern of this species from both locations showed that the shell length increased faster than its body weight (negative allometric pattern). The value of b as a derivative of growth indicates better conditions in the sample at Tanjung Manggewa than on Nusmapi Island. This difference in value can be an illustration of the condition of the M. annulus habitat and therefore information on the relationship between length and weight of growth patterns becomes important in efforts to monitor population conditions and their preservation in natural habitats.  Perairan pesisir Manokwari merupakan salah satu wilayah pesisir yang mengalami perkembangan kegiatan pembangunan yang sangat pesat dari tahun ke tahun. Kondisi ini dapat mengganggu ekosistem dan juga dapat mengganggu pertumbuhan gastropoda, khususnya  Monetaria annulus. Penelitian ini dilakukan di tiga lokasi (perairan Pantai Yenkarwar, Pulau Nusmapi, dan Tanjung Manggewa) selama dua bulan (Oktober dan November 2020). Tujuan dari penelitian ini yaitu untuk mendeskripsikan hubungan panjang dan berat, serta pola pertumbuhan gastropoda M. annulus di Teluk Doreri. Pengumpulan data dilakukan dengan menggunakan kuadrat dengan panjang 100 m dengan lebar yang disesuaikan dengan lebar hamparan lamun ke arah laut. Khusus untuk lokasi perairan Pantai Yenkarwar tidak ditemukan individu M. annulus selama sampling dilakukan. Hasil penelitian menunjukkan hubungan panjang dan berat pada lokasi P. Nusmapi dan Tanjung Manggewa secara berturut-turut, yaitu BT = 0,0017PC2,3883 dan BT = 0,0005PC2,8188. Pola pertumbuhan spesies ini dari kedua lokasi menunjukkan pertambahan panjang cangkang lebih cepat dibandingkan berat tubuhnya (pola alometrik negatif). Nilai b sebagai derivat dari pertumbuhan menunjukkan kondisi yang lebih baik pada sampel di lokasi Tanjung Manggewa dibandingkan Pulau Nusmapi. Perbedaan nilai ini bisa menjadi gambaran kondisi habitat M. annulus dan oleh karena itu informasi mengenai hubungan panjang dan berat pola pertumbuhan menjadi penting dalam upaya pemantauan kondisi populasi dan pelestariannya di habitat alami.